Defending the Pluralistic Minimum Universality of Human Rights - Burak Başkan (Culture and Civilization)
The idea of ‘universal human rights’ has emerged as a significant topic on the global agenda with the intensification of globalisation through technological change, the spread of transport and digital communication tools, and the increased visibility of instances of gross human rights violations in diverse regions worldwide. However, the spirit of the ‘Universal Declaration of Human Rights’, which emerged in the aftermath of the wave of fascism in 20th century Europe and the devastation of the Second World War, is still unable to penetrate all parts of the world. Furthermore, the rise of authoritarian populism in recent years has the potential to lead to a retreat from the idea of universal human rights. Thusly, the main purpose of this article is to introduce a viable, effective, pluralistic and minimum universal understanding of human rights on which world public opinion can agree. Within this framework, the intellectual elements of radical universalism and radical relativism, which are the parties to the debate on the universality of human rights, have been subjected to a rigorous analysis. A philosophical discussion was held in order to put forward an understanding of human rights that is respectful of multiculturalism and does not leave individuals at the mercy of the countries and societies in which they live, and to overcome the dichotomy in question. Moreover, the possible obstacles to the implementation of human rights worldwide have been discussed and the limits and scope of the pluralistic minimum universalist understanding of human rights have been revealed.